M-MDSC in vitro generation from mouse bone marrow with IL-3 reveals high expression and functional activity of arginase 1 - Aintablian, Arpa; Strozniak, Sandra; Heuer, Marion; Lutz, Manfred B. (Frontiers in Immunology, 2023)
Myeloid-derived suppressor cells (MDSC) represent major regulators of immune responses, which can control T cells via their inducible nitric oxide synthase (iNOS)- and arginase 1 (Arg1)-mediated effector functions. While GM-CSF is well documented to promote MDSC development, little is known about this potential of IL-3, an established growth factor for mast cells. Here, we show that IL-3, similar to GM-CSF, generates monocytic MDSC (M-MDSC) from murine bone marrow (BM) cells after 3 days of in vitro culture. At this time point, predominantly CD11b+ CD49a+ monocytic and CD11b+ CD49a- FcR I- neutrophilic cells were detectable, while CD11blow/neg FcR I+ mast cells accumulated only after extended culture periods. Both growth factors were equivalent in generating M-MDSC with respect to phenotype, cell yield and typical surface markers. However, IL-3 generated M-MDSC produced less TNF, IL-1 and IL-10 after activation with LPS + IFN- but showed higher Arg1 expression compared to GM-CSF generated M-MDSC. Arg1 was further induced together with iNOS after MDSC activation. Accordingly, an increased Arg1-dependent suppressor activity by the IL-3 generated M-MDSC was observed using respective iNOS and Arg1 inhibitors. Together, these data indicate that M-MDSC can be generated in vitro by IL-3, similar to GM-CSF, but with increased Arg1 expression and Arg1-mediated suppression capacity. This protocol now allows further in vitro studies on the role of IL-3 for MDSC biology.